First use of cenerimod, a selective S1P1 receptor modulator, for the treatment of SLE: a double-blind, randomised, placebo-controlled, proof-of-concept study - Viktoria Hermann; Anastas Batalov; Svetlana Smakotina; Pierre-Eric Juif; Peter Cornelisse (Lupus Science and Medicine)
Objective To investigate the pharmacodynamics, pharmacokinetics and safety of cenerimod—a potent, oral, selective sphingosine 1-phosphate 1 receptor modulator—in patients with SLE.Methods This multicentre, double-blind, placebo-controlled study was conducted in two parts. In part A, patients with SLE were randomised 1:1:1:1 to receive oral cenerimod 0.5, 1 or 2 mg, or placebo once daily for 12 weeks. Following an interim safety review of part A, additional patients were randomised 3:1 for part B and received cenerimod 4 mg or placebo once daily for 12 weeks. Endpoints included changes in total lymphocyte count, SLE Disease Activity Index-2000 (SLEDAI-2K) score (modified (mSLEDAI-2K) to exclude leucopenia), biomarker anti-double-stranded DNA (anti-dsDNA) antibodies, pharmacokinetic assessments and treatment-emergent adverse events (TEAEs).Results Part A included 49 patients (1:1:1:1 receiving cenerimod 0.5, 1 or 2 mg, or placebo) and part B included 18 patients (13 cenerimod; 5 placebo). Cenerimod caused a statistically significant dose-dependent reduction in total lymphocyte count from baseline to end of treatment (EOT). Compared with placebo at EOT, cenerimod 4 mg had an estimated treatment effect on change from baseline in mSLEDAI-2K score of −2.420 (p=0.0306), and on anti-dsDNA antibodies of −64.55 U/mL (p=0.0082), suggesting clinical and biological improvement in these exploratory efficacy analyses. Trough plasma concentrations were dose proportional and reached steady-state conditions after 4 weeks of once daily dosing. All groups reported similar, non-dose-related frequencies of TEAEs (cenerimod 0.5 mg: 41.7%; 1 mg: 41.7%; 2 mg: 46.2%; 4 mg: 38.5% and placebo: 58.8%). A small, dose-related, non-clinically relevant decrease in heart rate was only observed in the first 6 hours after initiation.Conclusions With an acceptable safety profile, the efficacy findings suggest that cenerimod has the potential to treat patients with SLE. Further investigation in larger patient populations with longer treatment duration is warranted.